DINAMIKA PSIKOLOGIS RESILIENSI PADA KORBAN GHOSTING - Siti Ulfi Rohmatin; Ny Sekar Yogi Estia Sari; Risky Ramadhanti; Neilam Nur Insani; Nurul Apriani (Academica: Journal of Multidisciplinary Studies, 2021)
The phenomenon of ghosting is widely interpreted as a way of avoiding and breaking away from relationships without including an explanation. Psychologist Jennice Vilhauer said that ghosting is a silent treatment, which in psychology is seen as emotional cruelty. The purpose of this study is to explain the resilience dynamics of individuals who are victims of ghosting in Solo Raya. This study uses qualitative methods with interviews and observations. The subjects of this research are four students who live in Solo Raya with an age range of 19-25 years who have been victims of ghosting. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. From the research, it was found that the subject had poor psychological dynamics. This can be seen from the negative changes in three aspects of psychological dynamics, namely cognitive, affective, and behavioral after experiencing a ghosting event. The resilience ability that is owned is quite good. This can be seen from four aspects, namely the ability to analyze problems, empathy, self-efficacy and positive self-achievement. However, there are three aspects that cannot be controlled by the subject, namely the ability to control emotions, control impulses and an attitude of optimism.Keywords: Ghosting; Psychological Dynamics; Resilience